Profil Guru Bk di MAN 1 cirebon - Mahmudah, Mahmudah; Janudi, Janudi (Jurnal Eksplorasi Bimbingan dan Konseling, 2023)
The initial thought that underlies this study is that the profile of the BK teacher must be known in advance so that counseling guidance can be applied properly according to the function of the BK teacher itself in every school, especially Madrasah Aliyah Negeri 1 Cirebon. The BK teacher profile is needed to find out the professional background of a BK teacher so that the duties, roles and competencies they have can be known. This type of research is qualitative, with a descriptive approach. Data collection techniques in this study using observation, interviews and documentation. The results of this study there are three Guidance and Counseling teachers who are in MAN 1 Cirebon, there is an organizational system of Guidance and Counseling teachers at MAN 1 Cirebon, the program of activities carried out includes the preparation of activity programs, Guidance and Counseling Programs, Guidance and Counseling Services and supporting activities, with the implementation of continuous guidance and counseling, it is hoped that students will be able to change their individual character better in the school environment, home environment and community environment. to be better.